Polityka ekologiczna jako instytucjonalny czynnik endogenicznego wzrostu gospodarczego - Dokurno, Zbigniew (Ecopolicy as an Institutional Factor of the Endogenous Economic Growth, 2006)
The paper is an attempt to create and prove the thesis presenting the relation between an institutional environmental policy and characteristics of the theory of endogenous growth. The main emphasis was put on relations determining the pace of growth. The presented conception is a proof of growing importance of New Institutional Economics in solving many economic problems. The paper presents also specific solutions in the form of models of endogenous growth as an alternative to classic models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 183-200